From coconut to land: changing livelihoods in Micaúne, Central Mozambique - Adalima,José Laimone (2022)
Abstract This paper is about how people in Micaúne currently generate their livelihoods in the aftermath of the coconut economy, which collapsed in the 2000s due to the upsurge of the coconut lethal yellowing disease (CLYD) in the early 1990s. This created uncertainty among residents; however, they did not migrate in masses as documented in the literature on livelihood shocks. On the contrary, Micaúne residents have adopted a different strategy of waiting and observing, since they believe that their future lies in their land because of the potential wealth that could possibly materialise from their subsoil (anticipation). This highlights a major shift of land from a mere host for palm trees into a valuable commodity.